Pembentukan Karakter melalui Pendidikan Agama Islam - Kisman Kisman (AL-FURQAN, 2021)
This paper discusses the role of Islamic religious education in schools in character building for students. Islamic Religious Education (PAI) is one of the most important pillars of character education. Character education will grow well if it starts from the installation of a religious spirit in children, therefore Islamic education material in schools is one of the supports for character education. Through PAI learning, students are taught aqidah as the basis for their religion, taught al-Quran and al-hadith as their life guidelines, taught fiqh as legal signs in worship, teaching Islamic history is an example of life, and teaches morals as a guide for human behavior whether in the category good or bad. Therefore, the main purpose of PAI learning is the formation of personalities in students which are reflected in their behavior and thought patterns in everyday life. Besides that, the success of Islamic Education learning in schools is also determined by the application of appropriate learning methods